Attenuation of some subjective effects of amphetamine following tyrosine depletion. - McTavish, S; McPherson, M; Sharp, T; Cowen, P (1999)
Fifteen healthy volunteers received d-amphetamine (20 mg orally) 2 h after ingesting either a nutritionally balanced amino acid mixture or one lacking the catecholamine precursors, tyrosine and phenylalanine (TYR-free). Plasma tyrosine levels were significantly lowered in subjects who received the TYR-free mixture but mean plasma amphetamine levels were higher. Despite this, the TYR-free mixture appeared to decrease the subjective psychostimulant effects of amphetamine, as determined by visual analogue scales. In contrast, the TYR-free mixture failed to lower the subjective anorectic effect of amphetamine. These findings are consistent with animal experimental studies indicating that tyrosine depletion attenuates the release of dopamine produced by amphetamine but not the release of noradrenaline.